Esquemas preferenciales de comercio con los Estados Unidos y la Unión Europea: Éxito o fracaso para las exportaciones no tradicionales bolivianas? - Ana Lucia Vidaurre Valdivia (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2019)
– This research applies the gravity model to explore the main determinants of volume of Bolivian non-traditional exports. This study emphasizes the impact generated by subscriptions to commercial and preferential trade treatments with the European Union and the United States. For this purpose, a panel data analysis is carried out for the 28 countries of the UE block, the United States and 32 other countries to which Bolivia exported during the period 1992-2017. The outcomes unveil expected signs according to theory. Finally, in the case of trade impacts, main findings reveal that subscriptions effects to commercial and preferential schemes in the case of ATPDEA with the United States (concluded in 2008) and the GSP with the UE (currently in effect) provides a positive impact on the volume of non-traditional Bolivian external sales.
Keywords: F14; F1; 330; Commercial integration; gravity model; non-traditional exports; trade agreements and preferential schemes